An AFM study of the interaction between an ?-alumina particle and a flat sapphire surface in high ionic strength electrolyte solutions - Yilmaz, Hüseyin; Sato, Kimiyasu; Watari, Koji (My University, 2007)
A colloid probe method has been used to characterize the normal and lateral forces between a hydrophilic ?-alumina particle and a c-sapphire surface (0001) at pH 11 in various KCl electrolyte concentrations. The normal forces are repulsive at all ionic strengths measured. The electrical double layer thickness is compressed at high electrolyte concentrations, which is evident from the decrease in the interaction distances observed in the force-distance curves. At high electrolyte concentrations, the friction forces decrease between the alumina surfaces due to the lubricating effect of the hydrated cations. © 2009 Elsevier B.V., All rights reserved.
2nd International Conference on Characterization and Control of Interfaces for High Quality Advanced Materials, and Joining Technology for New Metallic Glasses and Inorganic Materials -- Kurashiki -- 74707
Keywords: Colloids; Corundum; Electric properties; Electrolysis; Electrolytes; Flow interactions; Glass; Hydrated alumina; Hydrates; Ionic strength; Joining; Liquid metals; Metallic glass; Quality control; Sapphire; Alumina particles; Alumina surfaces; Colloid probes; Electrical double layers; Electrolyte concentrations; Electrolyte solutions; Friction forces; Hydrated cations; Interaction distances; Lateral forces; Lubricating effects; Normal forces; Sapphire surfaces; Surfaces